2020
DOI: 10.1088/1748-9326/ab93f9
|View full text |Cite
|
Sign up to set email alerts
|

A carbon monitoring system for mapping regional, annual aboveground biomass across the northwestern USA

Abstract: This paper presents a prototype Carbon Monitoring System (CMS) developed to produce regionally unbiased annual estimates of aboveground biomass (AGB). Our CMS employed a bottom-up, two-step modeling strategy beginning with a spatially and temporally biased sample: project datasets collected and contributed by US Forest Service (USFS) and other forestry stakeholders in 29 different project areas in the northwestern USA. Plot-level AGB estimates collected in the project areas served as the response variable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…AGB models were fit using the ranger R package's implementation of the random forest algorithm (Breiman, 2001;Wright and Ziegler, 2017), a popular machine learning technique for predicting forest biomass across landscapes (see for instance Huang et al, 2019;Hudak et al, 2020). Separate models were fit on predictors calculated using each level of ground noise filtering ("unfiltered," "ground," "0.1m," "1m," and "2m" thresholds)…”
Section: Model Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…AGB models were fit using the ranger R package's implementation of the random forest algorithm (Breiman, 2001;Wright and Ziegler, 2017), a popular machine learning technique for predicting forest biomass across landscapes (see for instance Huang et al, 2019;Hudak et al, 2020). Separate models were fit on predictors calculated using each level of ground noise filtering ("unfiltered," "ground," "0.1m," "1m," and "2m" thresholds)…”
Section: Model Fittingmentioning
confidence: 99%
“…However, there exists some disagreement about precisely which returns to aggregate when computing these statistics. While some LiDAR-based AGB models include all returns when calculating summary statistics (Hudak et al, 2020), others first filter out returns below various height thresholds when calculating percentile heights (Ma et al, 2018), density percentiles (Huang et al, 2019), or their entire suite of predictors (García et al, 2010). Filtering is typically described as being done to remove ground noise from return data, in order to avoid having "ground" returns mask any signal contained in the remaining "canopy" returns.…”
Section: Introductionmentioning
confidence: 99%
“…While reviewing earlier research applying two sequential regression models in their modelling strategy, we noted a variety of terms describing the same concept in the literature. While we choose to refer to this as a sequential regression approach, we additionally found the following use of terminology: two-step modelling strategy [42], [44], [54], two-stage regression [39], [41], twostage up-scaling method [23], [34], two-phase estimator [36], two-phase (or three-phase) sampling design [31], [38], hybrid and hierarchical model-based inference [37], [40], three-phase design [35]. Additionally, [32], [33], [43], [53], [55], [56] also apply a modelling approach with two sequential regression models without labelling it by any particular term.…”
Section: B Data Fusion With Two Sequential Regression Modelsmentioning
confidence: 99%
“…Most of the previous research that we identified focus on relating ground reference data to ALS, and then relate ALS-derived AGB estimates to spaceborne LiDAR data [31], [35], [36], [38], [53], [55] or a combination of different sensors [23], [33], [34], [37], [40], [42], [56]. Some other relate the ALS-derived AGB estimates to a single sensor, such as Sentinel-2 [41], [43], Landsat [39], [44], GEDI Lidar [42], ALOS PALSAR, [54] or SRTM X-band radar [32].…”
Section: B Data Fusion With Two Sequential Regression Modelsmentioning
confidence: 99%
“…Carbon has been successfully estimated using derived spectral metrics from multispectral satellite imagery [32][33][34], structural metrics from light detection and ranging (LiDAR) data [35][36][37][38], or a combination of the two [39][40][41] in correlative models linking these metrics with field data and has become a common source for carbon estimation at regional scales. Access to multitemporal remote sensing data provides additional opportunities to measure change in carbon stocks over time; however regional analyses assessing carbon dynamics have focused on upland forests (e.g., [42][43][44][45]), herbaceous marsh (e.g., [46]), and mangrove forests (e.g., [47,48]) and not temperate coastal forests (however, see [49]). These studies also do not quantify the combined effects of the natural and anthropogenic factors driving carbon variability and change at regional scales, nor do they account for the spatial heterogeneity in the strength of the relationships between drivers and aboveground carbon stocks by implementing appropriate spatial modeling approaches.…”
Section: Introductionmentioning
confidence: 99%